Portrait of Intersectional Feminism in The Movie - Eva Solina Gultom; La Ode Darfin; Rasiah Rasiah (Yayasan Adra Karima Hubbi, 2024)
Background. Intersectional studies are often associated with political efforts to understand the interconnections between gender, class and race. Antonia Brico as the main character shows a strong ambition to become a famous conductor in classical music despite getting rejection from men, financial difficulties, and social pressure. Purpose. This research aims to analyze the various forms of discrimination faced by women in The Conductor movie, focusing on the intersectional feminist theory proposed by Kimberly Crenshaw. Method. This study employs descriptive qualitative methodologies. The dataset for this research consists of 14 instances of discrimination against women, as well as the portrayal of women's efforts to attain gender equality in the movie. These data are utilized by researchers to facilitate the analysis process. Results. The researchers identified multiple instances of discrimination encountered by women, particularly the protagonist Antonia Brico, who faced challenges from different sources. One example of this is the strong urge and motivation to advocate for women's rights in society, particularly in the position of leadership, within the realm of music. In addition, this movie presents other issues, including social, cultural, and political challenges that are primarily connected to Antonia Brico's personal battle. Conclusion. Brico shows her intellectual ability by studying with renowned musicians and conductors, even studying abroad, to gain knowledge and achieve her goals. She also demonstrates the courage to self-actualize, which is shown by her efforts to challenge perspectives that undermine women, such as the belief that women cannot lead and must hold positions below men. In addition, she also showed patience and tenacity in facing all the obstacles of oppression and discrimination that occurred.